Comparison in Europe of telco value evolution during 'bubbles': Dotcom 2000 vs. Dotcom 2012 - Fernando Herrera-González (International Telecommunications Society (ITS), 2014)
During the last years, a surge in values related to the New Economy has occurred. This phenomenon is similar to the 2000 Dotcom bubble, even if in those years the value growth was fuelled by other firms and entrepreneurs. What both 'bubbles' have in common is that, in both cases, they are based on activities that rely or have need of telecommunication infrastructures. According to economic theory, the value of downstream goods is driven by the value given by individuals to end goods. Because of this, the value of the telecommunications infrastructure should somehow reflect the value of Dotcom services, as telecommunication networks are needed for the production of Dotcom services. This paper explores the relative evolution of telecommunications value in Europe with respect to the Dotcom services during the Dotcom 2000 Bubble and the recent re-surge of the Dotcom sector. In both periods, the value of European telecommunication operators should have followed the increase in value of Dotcom services. However, this was not the case. In order to explain the phenomenon, we consider the evolution of the factors that induce value in the free market (utility, availability) and its interaction with the evolution of telecommunication regulation in Europe.
Keywords: 330